(untitled) (BIRDEM Medical Journal, 2026)
Background: In breast conserving surgery (BCS), large defects in the upper inner quadrant, named the no man’s land of the breast, causes shift of the nipple in an unnatural upward or medial fashion. There is every possibility to develop an untoward deformity. There are many oncoplastic options but lumps distant from nipple areolar complex (NAC) are challenging to tackle. Here we are report 2-year follow-up result after dermoglandular rotation flap (DGRF) with a Burows triangle technique in managing upper inner quadrant breast cancer. Methods: This prospective observational study was done at BIRDEM General Hospital. Over a period of three years (August 2020 to July 2023), seven patients were selected for DGRF technique, depending on location and size of lump, distance from NAC and skin, breast ptosis and breast size. The lump was resected with a full thickness skin to pectoral fascia, rectangle or isosceles triangle with its apex towards NAC. Dermoglandular flap was released by a curvilinear lateral extension of the base of the triangle upto mid-axillary line. A small triangular tissue was excised in axilla to facilitate flap advancement. This also provides access to axilla. Axilla was dealt with sentinel lymph node biopsy (SLNB) or axillary lymph node dissection (ALND) procedures as needed. Patients were discharged after 48 hours and followed according to a standard follow-up schedule. Results: Total patients were 7 with age between 42 and 59 years. Tumours were located 7-11 cm from NAC. One patient received neoadjuvant chemotherapy (NACT) before surgery. Four patients were negative for SLNB on frozen biopsy. Time of operation was 90 to 120 minutes. All received post-operative chemo-radiation and hormone therapy as indicated. One patient died five months after surgery, while getting her 4th cycle of chemotherapy. Six patients remained disease free with good cosmetic outcome after 2 years follow-up. Conclusion: For upper inner quadrant breast cancer, DGRF (with or without donut), is an easily reproducible oncoplastic breast conserving technique. It also gives easy access to axilla and results in a very good symmetry. Considering our social circumstances, in carefully selected cases, DGRF is a practical technique in Bangladesh. BIRDEM Med J 2026; 16(1): 25-32